2011
DOI: 10.1007/s10545-011-9393-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enzyme replacement therapy on five patients with advanced late‐onset glycogen storage disease type II: a 2‐year follow‐up study

Abstract: We examined the efficacy of 2-year enzyme replacement therapy (ERT) using recombinant human α-glucosidase (GAA; Myozyme®) in five long-term ventilator-dependent adults and aged patients with advanced, late-onset glycogen storage disease type II (GSDII, also known as Pompe disease). Although all patients had advanced respiratory failure and were ventilator-dependent for more than 6 years, four showed obvious improvements in muscle strength, pulmonary function, and activities of daily living after ERT. Improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 20 publications
(19 reference statements)
4
22
0
1
Order By: Relevance
“…Only one patient (number 17) showed a decline in both pulmonary function tests. We did not document the FVC % improvement in the first year as it was shown beforehand [6,16,17,24] but we documented a noticeable overall upward trend in FVC% supine and SNIP results measured over time (Figs. 2, 3).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Only one patient (number 17) showed a decline in both pulmonary function tests. We did not document the FVC % improvement in the first year as it was shown beforehand [6,16,17,24] but we documented a noticeable overall upward trend in FVC% supine and SNIP results measured over time (Figs. 2, 3).…”
Section: Discussionmentioning
confidence: 64%
“…Over a period of 78 weeks, treatment with alglucosidase alpha resulted in an improved walking distance on the 6MWT and stabilization of pulmonary function, meeting both primary endpoints of the trial [6]. ERT maintained efficacy for 2 years [5] that resulted in stabilization of VCmax following ERT for 3 years and longer in LOPD patients [16,17,18]. There are additional reports showing significant improvement in pulmonary function, preventing or delaying ventilator dependency and prolonging survival [6,18,[19][20][21][22][23][24]25] and led to fewer hospital admissions [24].…”
Section: Introductionmentioning
confidence: 83%
“…However, two other case reports (Furusawa et al 2012;Ishigaki et al 2012) did not find significant improvement in MMT after ERT. The two patients reported by Furusawa et al had severe disease requiring ventilation, while a 10-year-old boy reported by Ishigaki et al (2012) (first signs of JOPD at age 2) showed only minimal change on the MMT after 6 months of ERT compared to baseline.…”
Section: Gross Motor Functionmentioning
confidence: 78%
“…case report 1 (Winkel et al 2004) was reported as improved after 3 years of ERT from 14% (value not reported, reported here as 15%); measurements illustrated here for case reports 3 and 4 (Orlikowski et al 2011) and 11 (Papadimas et al 2011) were taken in the sitting position; case report 7 (Ishigaki et al 2012) improved after 4 months ERT from 57 to 65% but was reported to return to baseline after 18 months (no value given, reported here as 57%); Korpel et al (2009) case showed no improvement after 6 months ERT from 26% at baseline (value not reported). Case notes B: data for case reports 6 and 7 (Furusawa et al 2012) were rounded to the nearest whole number for the purpose of reporting here FVC scores over 80% are considered to be within the normal range (Lachmann and Schoser 2013), so at baseline, three of the five patients were considered to have normal respiratory functioning. One patient who had much lower capacity at baseline than the others measured a significant increase in capacity over that time period (increase from 14 to 30%).…”
Section: Cardiorespiratory Functionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] More recently, in a randomized study of ERT in LOPD adults, muscular and pulmonary functions reached their greatest improvement in the first 6 months, then stabilized through 18 FIGURE 1. Enhanced paranasal sinus CT shows a 3.1 3 2.3-cm low-density well-encapsulated mass lesion in the right lateral pterygoid muscle.…”
mentioning
confidence: 98%